Virtual adaptation of traditional healthcare quality improvement training in response to COVID-19: a rapid narrative review - Zuneera Khurshid; Aoife De Brún; Gemma Moore; Eilish McAuliffe (BMC, 2020)
Abstract Background Information and communication technology are playing a major role in ensuring continuity of healthcare services during the COVID-19 pandemic. The pandemic has also disrupted healthcare quality improvement (QI) training and education for healthcare professionals and there is a need to rethink the way QI training and education is delivered. The purpose of this rapid evidence review is to quickly, but comprehensively collate studies to identify what works and what does not in delivering QI training and education using distance learning modalities. Methods Three healthcare databases were searched along with grey literature sources for studies published between 2015 and 2020. Studies with QI training programmes or courses targeting healthcare professionals and students with at least one component of the programme being delivered online were included. Results A total of 19 studies were included in the review. Most studies had a mixed methods design and used blended learning methods, combining online and in-person delivery modes. Most of the included studies reported achieving desired outcomes, including improved QI knowledge, skills and attitudes of participants and improved clinical outcomes for patients. Some benefits of online QI training delivery include fewer required resources, reduced need for on-site instructors, increased programme reach, and more control and flexibility over learning time for participants. Some limitations of online delivery modes include limited learning and networking opportunities, functional and technical problems and long lead time for content adaptation and customisation. Discussion The review highlights that distance learning approaches to QI help in overcoming barriers to traditional QI training. Some important considerations for those looking to adapt traditional programmes to virtual environments include balancing virtual and non-virtual methods, using suitable technological solutions, customising coaching support, and using multiple criteria for programme evaluation. Conclusion Virtual QI and training of healthcare professionals and students is a viable, efficient, and effective alternative to traditional QI education that will play a vital role in building their competence and confidence to improve the healthcare system in post-COVID environment.